Ways of Reforming Entrepreneurship Stimulation Tax System in RA - Shmavonyan, Garegin (Bulletin of Yerevan University G: Economics, 2013)
The contemporary period of Armenia’s socio-economic development actualizes the problems of tax system radical reform aimed at the attractive business environment formation, qualitative economic growth ensuring. The author substantiates exhausting of tax administration infinite “improving” that cannot facilitate shadow circulation decrease, economy growth basically because of action of fiscal but not incentive function of tax system. In this connection the article reveals profound factors stipulating radical tax reform priority. Decrease of tax burden, giving “tax holidays” are considered as a tax reform pivotal vector because just the latter can insure qualitative breakthrough in economic development. The author also propounds the basic ways of Armenia’s tax system reforming.